Is frailty associated with long-term survival, neurological function and patient-reported outcomes after in-hospital cardiac arrest? – A Swedish cohort study. (October 2022) - Jonsson, Hanna; Piscator, Eva; Israelsson, Johan; Lilja, Gisela; Djärv, Therese
Abstract: Background: Frailty is associated with poor 30-days survival after in-hospital cardiac arrests (IHCA). The aim was to assess how pre-arrest frailty was associated with long-term survival, neurological function and patient-reported outcomes in elderly survivors after IHCA. Methods: Patients aged ≥ 65 years with IHCA at Karolinska University Hospital between 2013–2021 were studied. Frailty was assessed by the Clinical Frailty Scale (CFS) based on clinical records and categorised into non-frail (1–4) or frail (5–7). Survival was assessed in days. Neurological function was assessed by the Cerebral Performance Category scale (CPC). A telephone interview was performed six months post-IHCA and included the questionnaires EuroQoL-5 Dimensions-5 Levels and Hospital Anxiety and Depression Scale. Results: Totally, 232 (28%) out of 817 eligible patients survived to 30-days. Out of 232, 65 (28%) were frail. Long-term survival was better for non-frail than frail patients (6 months (92% versus 75%, p-value < 0.01), 3 years (74% vs 22%, p-value < 0.01)). The vast majority of both non-frail and frail patients had unchanged CPC from admittance to discharge from hospital (87% and 85%, respectively, p-value 0.52). The 121 non-frail patients reported better health compared to 27 frail patients (EQ-VAS median 70 versus 50 points, p-value < 0.01) and less symptoms of depression than frail (16% and 52%, respectively, p-value < 0.01). Conclusion: Frail patients suffering IHCA survived with the same neurological function they had at admittance. Although one in five frail patients survived to three years, frailty was associated with a marked decrease in long-term survival as well as increased symptoms of depression and poorer general health.